Tinjauan Pustaka: Kinerja Kondensor terhadap Produksi Air Tawar pada Proses Desalinasi Air Laut - Ahmad Faiz Rahmatullah; Dan Mugisidi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
The utilization of waste heat from air conditioning (AC) systems has the potential to serve as an alternative energy source for seawater desalination processes. However, the thermal efficiency of desalination systems is strongly influenced by the condensation stage, particularly by the shape and design of the condenser used. This review aims to examine and compare various condenser configurations such as shell and tube, coiled tube, plate, and finned condensers in the context of improving condensation efficiency and freshwater production. The study is conducted through a literature analysis that reviews key parameters such as heat transfer rate, coolant flow rate, and temperature differences between fluids. The review results show that shell and tube condensers provide the highest heat transfer effectiveness, while plate condensers offer better energy efficiency and ease of maintenance. In conclusion, selecting the appropriate condenser design can significantly enhance the efficiency of seawater desalination systems utilizing AC waste heat.